2022
DOI: 10.3389/fmicb.2022.842106
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure Reveal Cryptic Genetic Variation and Long Distance Migration of Puccinia graminis f. sp. tritici in the Indian Subcontinent

Abstract: Stem rust caused by Puccinia graminis f. sp. tritici (Pgt) is a devastating disease of wheat worldwide since time immemorial. Several wheat stem rust outbreaks have been reported worldwide including India. Approximately 7 mha wheat area in central and peninsular India is highly vulnerable to stem rust epidemics. In this study, a repository of 29 single genotype uredospore pathotypes, representing five geographical regions, was characterized by investigating their virulence phenotype and simple sequence repeat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
3
3
0
Order By: Relevance
“…The molecular grouping of Pgt pathotypes, generated through unweighted neighbor-joining (NJ) cluster analysis in DARwin 6.0.14, corroborated, up to some extent, virulence-based grouping of these pathotypes, which was in agreement with our previous findings (Prasad et al, 2022). Pathotypes 21, 21-1, and 21A-2;11 and 11A;117 and 117-6;and 40A, 40-2, and 40-3, sharing almost matching avirulence/virulence structure as reported previously (Prasad et al, 2018;Prasad et al, 2022), were clustered in one MG/subgroup (Figure 4). Such an association of virulence phenotypes and SSR genotypes among P. triticina (Wang et al, 2010) and P. striiformis tritici (Hovmoller et al, 2002) isolates is also reported, which is not uncommon if the genes responsible for virulence/pathogenicity are extensively distributed in pathogen genome (Ordonez and Kolmer, 2009).…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…The molecular grouping of Pgt pathotypes, generated through unweighted neighbor-joining (NJ) cluster analysis in DARwin 6.0.14, corroborated, up to some extent, virulence-based grouping of these pathotypes, which was in agreement with our previous findings (Prasad et al, 2022). Pathotypes 21, 21-1, and 21A-2;11 and 11A;117 and 117-6;and 40A, 40-2, and 40-3, sharing almost matching avirulence/virulence structure as reported previously (Prasad et al, 2018;Prasad et al, 2022), were clustered in one MG/subgroup (Figure 4). Such an association of virulence phenotypes and SSR genotypes among P. triticina (Wang et al, 2010) and P. striiformis tritici (Hovmoller et al, 2002) isolates is also reported, which is not uncommon if the genes responsible for virulence/pathogenicity are extensively distributed in pathogen genome (Ordonez and Kolmer, 2009).…”
Section: Discussionsupporting
confidence: 70%
“…The availability of Sr31 and other known and unknown Sr genes in recently developed wheat varieties, effective against all known pathotypes of stem rust in India and neighboring countries, accompanied by poor rainfall and a significant reduction in relative humidity over the years could have hampered the survival and infection rate of the natural population of Pgt and, therefore, poor stem rust incidence (Ayliffe et al, 2008;Prank et al, 2019). As revealed previously (Prasad et al, 2018;Prasad et al, 2022), the Pgt population reported from India and Nepal remained avirulent to Sr7a, Sr26, Sr27, Sr31, Sr32, Sr33, Sr39, Sr40, Sr43, SrTmp, and SrTt3 to date. Some of these genes, for instance, Sr26, have been found to be effective against the Pgt population including Ug99 globally.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations